Pertumbuhan dan Perkembangan Anak Usia 6-24 Bulan - Diana Wati, Ni Luh Gede; Rismawan, Made; Sriasih, Ni Kadek (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Stunting is one of the problems due to inadequate supervision of growth and development in children; thus, it is necessary to supervise children regularly and appropriately in order to reduce the incidence of stunting. Early detection of growth and development is important in determining a child's growth and development, both in spirit, attitude, and actions. If stunting prevention is not carried out through early detection of growth and development in children, the child's growth and development can be disrupted. The aim of this research is to describe the growth and development of children aged 6-24 months in the working area of Public Health Center I West Denpasar. This study employed descriptive design with cross-sectional approach. The study was carried out in the working area of Public Health Center I West Denpasar in April 2024. There were 224 respondents recruited as the sample through purposive sampling technique. The data were collected using observation sheets and Development Pre-Screening Questionnaire. This study used descriptive data analysis based on frequency and percentage results. Moreover, this study has been ethically approved by the ITEKES Bali ethics commission.The findings showed that the growth of children was majorly in the good category with 195 respondents (87,1%). Furthermore, the development of the children was majorly in the good category with 219 respondents (97,8%). The growth and development of respondents are majorly in the good category. Thus, monitoring children's growth and development needs to be carried out periodically.